Handbook of electrical engineering : for practitioners in the oil, gas, and petrochemical industry - Sheldrake, Alan L. (Wiley, 2003)
A practical treatment of power system design within the oil, gas, petrochemical and offshore industries. These have significantly different characteristics to large-scale power generation and long distance public utility industries. Developed from a series of lectures on electrical power systems given to oil company staff and university students, Sheldrake's work provides a careful balance between sufficient mathematical theory and comprehensive practical application knowledge.